Development, validity, and reliability of a questionnaire on mothers’ knowledge in complementary feeding practices (PI-MPASI) in Indonesia - Andriani, Rini; Supriyatno, Bambang; Kekalih, Aria; Sjarif, Damayanti Rusli (Paediatrica Indonesiana, 2023)
Background A number of complementary educational feeding modules have been circulating in the community, but mothers have yet to use them optimally. There is an urgent need for an effective educational method on appropriate complementary feeding and an instrument to measure maternal knowledge in proper complementary feeding practices. Objective To develop and assess the validity and reliability of a questionnaire on complementary feeding practices. Methods We conducted a qualitative study to develop a questionnaire followed by a cross-sectional study to test the validity and the reliability of the PI-MPASI questionnaire. The research team designed the PI-MPASI questionnaire through a literature review with a team of experts, based on the evidence-based feeding practice recommendations for infants and toddlers in Indonesia as compiled by the Indonesian Pediatric Society (IPS) in 2015. Content validation was carried out through expert review, whilst the construct validity and the reliability were tested on 110 mothers who met the inclusion criteria. Results In the content validity assessment, an average congruent percentage of 90% was obtained for the sub-themes of time, nutritional adequacy, safety, and feeding responsiveness as the four essential points that mothers should know regarding proper complementary feeding practices. Most of the item scores showed moderate to high correlations with the total score, with reliability test showcasing a good internal consistency (Cronbach's alpha = 0.715). Conclusion This study showed that our questionnaire on mothers’ knowledge in complementary feeding practices (PI-MPASI) is a valid and reliable instrument to assess maternal knowledge on correct complementary feeding practices in Indonesia.